BIOPSY SITE AND HISTOPATHOLOGY IN DIAGNOSING BENIGN AND MALIGNANT GASTROINTESTINAL CONDITIONS. : JPUMHS; 2025:15:01,129-136. http://doi.org/10.46536/jpumhs/2025/15.01.606 - Saima Nadeem1, Muhammad Tariq Hamayun Khan2, Faiqa Mubeen3, Sana Ullah Khan4, Arshad Khan5, Mohammad Tahir6 , (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2025)
BACKGROUND: Gastrointestinal illnesses exhibit a broad range of histological findings, with malignancies and benign ailments differing throughout age demographics. Precise identification of biopsy kinds, locations, and histological results is essential for diagnosis and treatment. OBJECTIVE: This study aims to investigate the distribution of benign and malignant gastrointestinal lesions by age group, biopsy type, and histological results, as well as their correlations. MATERIALS AND METHODS: A cross sectional study was conducted on 159 patients undergoing gastrointestinal biopsies in Khyber Teaching Hospital, Peshawar. Variables included patient age groups, biopsy types (colonoscopy, endoscopic), biopsy sites, and histopathological diagnoses. Frequency, percentages, and chi-square tests were used to evaluate associations, with logistic regression applied for malignancy prediction. RESULTS: Most samples were endoscopic (88.7%), with the stomach site being the predominant location (54.7%). Benign lesions constituted 87.4% of patients, whereas cancers represented 12%. The greatest frequency of benign lesions occurred in the 20-30 age group (100% positive), but malignancies were more prevalent in older demographics, however without any correlation (p=0.168). Histopathologically, chronic non-granulomatous colitis (CNCG) was the most prevalent benign finding, occurring in 43.3% of cases. Dyspepsia was a prevalent symptom, occurring in 15.7% of cases. Substantial relationships were identified between benign status and age group (p=0.024), however malignant status exhibited no significant link with age. Logistic regression identified age and biopsy type were significant predictors of malignancy. CONCLUSION: This study emphasizes the prevalence of benign gastrointestinal lesions in younger individuals and the significance of age and biopsy type in assessing malignancy risk. Histopathological examination is critical for correct diagnosis and clinical decision-making.